Allosteric activators of cystathionine γ lyase to augment endogenous hydrogen sulfide and inhibit pathologic calcification - Sonia Nasi; Driss Ehirchiou; Cindy Blatter; Veronique Chobaz; Stefan Germann; Alexandra Brandenberger; Elias Bommeli; Emiko Uchikawa; Giuseppe Cirino; Rainer Riedl; Alexander So; Nathalie Busso (Pharmacological Research)
Hydrogen sulfide (H₂S), a gasotransmitter naturally produced in the body by enzymes such as cystathionine γ lyase (CSE), helps reduce inflammation, oxidative stress, and abnormal tissue calcification. We present a novel strategy to boost endogenous H₂S production via CSE allosteric activation. Two CSE positive allosteric modulators (CSE-PAMs) were identified. Despite moderate binding affinity, both compounds induced a strong allosteric effect, increasing H₂S production by approximately 200 %. Cryo-electron microscopy and proteomics identified a distinct allosteric binding pocket on recombinant human CSE. In cellular assays, both compounds elevated H₂S levels. This correlated with inhibition of calcification. In chondrocytes, CSE-PAMs reduced alkaline phosphatase activity, inflammatory cytokine secretion, and oxidative stress, while enhancing protein persulfidation. These results highlight CSE-PAMs as promising therapeutic agents for conditions involving pathological calcification and inflammation, such as osteoarthritis. Additionally, they serve as valuable tools for investigating CSE-derived H₂S biology, previously limited by a lack of specific modulators.